THE ROLE OF COMPANY PERFORMANCE MODERATING CAPITAL STRUCTURE AND COMPANY EXTERNAL FACTORS ON COMPANY VALUE IN THE CONSISTENCY OF THE ECONOMIC RECESSION in 2020 - Purnamasari, Puji Endah; Sartika, Farahiyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
An increase in inflation can cause a slowdown or decrease in a country's economic growth, this situation can be called a recession in a country. The decline in the exchange rate of the domestic currency with foreign currencies and the increase in gross domestic product for two quarters, caused many companies to experience losses due to decreased sales and losses experienced by these companies resulted in a decrease in the value of the company which was marked by a decrease in the company's stock price. This study aims to measure the effect of capital structure, inflation, exchange rate, gross domestic product on firm value with firm performance as a moderating variable. The results of this study indicate that capital structure and inflation do not have a significant impact on firm value while the exchange rate and gross domestic product have a significant positive impact on firm value. While the company's performance is not able to modernize the relationship between the independent variable and the dependent variable.